![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
1) \(\Rightarrow\left[{}\begin{matrix}x=-3\\x=5\end{matrix}\right.\)
2) \(\Rightarrow5\left(x-2\right).3\left(x+2\right)=0\Rightarrow\left[{}\begin{matrix}x=2\\x=-2\end{matrix}\right.\)
3) \(\Rightarrow2\left(x-4\right)\left(x-7\right)=0\Rightarrow\left[{}\begin{matrix}x=4\\x=7\end{matrix}\right.\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(-7.\left(3x-5\right)+2.\left(7x-14\right)=28\)
\(\Leftrightarrow-21x+35+14x-28=28\)
\(\Leftrightarrow-7x+7=28\)
\(\Leftrightarrow-7x=21\)
\(\Leftrightarrow x=-3\)
Vậy \(x=-3\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{3x}{2\cdot5}+\frac{3x}{5\cdot8}+\frac{3x}{8\cdot11}+\frac{3x}{11\cdot14}=\frac{1}{21}\)
\(=>\frac{3x}{3}\left[\frac{3}{2\cdot5}+\frac{3}{5\cdot8}+\frac{3}{8\cdot11}+\frac{3}{11\cdot14}\right]=\frac{1}{21}\)
\(=>x\left[\frac{3}{2\cdot5}+\frac{3}{5\cdot8}+\frac{3}{8\cdot11}+\frac{3}{11\cdot14}\right]=\frac{1}{21}\)
\(=>x\left[\frac{1}{2}-\frac{1}{5}+\frac{1}{5}-\frac{1}{8}+...+\frac{1}{11}-\frac{1}{14}\right]=\frac{1}{21}\)
\(=>x\left[\frac{1}{2}-\frac{1}{14}\right]=\frac{1}{21}\)
\(=>x\cdot\frac{3}{7}=\frac{1}{21}\Leftrightarrow x=\frac{1}{9}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) => 4/3x = 7/9 - 4/9 = 1/3
=> x = 1/3 : 4/3 = 1/4
b) => 5/2 - x = 9/14 : (-4/7) = -9/8
=> x = 5/2 - (-9/8) = 5/2 + 9/8 = 29/8
c) => 3x = 2 và 2/3 - 3/4 = 8/3 - 3/4 = 23/12
=> x = 23/12 : 3 = 23/36
D) => -5/6 - x = 1/4
=> x = -5/6 - 1/4 = -13/12
a) \(\dfrac{4}{9}+\dfrac{4}{3}x=\dfrac{7}{9}\)
\(\dfrac{4}{3}x=\dfrac{7}{9}-\dfrac{4}{9}=\dfrac{1}{3}\)
\(x=\dfrac{1}{3}:\dfrac{4}{3}\)
\(x=\dfrac{1}{4}\)
b) \(\left(\dfrac{5}{2}-x\right)\left(-\dfrac{4}{7}\right)=\dfrac{9}{14}\)
\(\dfrac{5}{2}-x=\dfrac{9}{14}:\left(-\dfrac{4}{7}\right)=-\dfrac{9}{8}\)
\(x=\dfrac{5}{2}-\left(-\dfrac{9}{8}\right)\)
\(x=\dfrac{29}{8}\)
c) \(3x+\dfrac{3}{4}=2\dfrac{2}{3}\)
\(3x+\dfrac{3}{4}=\dfrac{8}{3}\)
\(3x=\dfrac{8}{3}-\dfrac{3}{4}=\dfrac{23}{12}\)
\(x=\dfrac{23}{12}:3\)
\(x=\dfrac{23}{36}\)
d) \(-\dfrac{5}{6}-x=\dfrac{7}{12}+\dfrac{-1}{3}\)
\(-\dfrac{5}{6}-x=\dfrac{1}{4}\)
\(x=-\dfrac{5}{6}-\dfrac{1}{4}\)
\(x=-\dfrac{13}{12}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
22.23-(56:54-20100.24)3-14
= 25-(52-1.24)3-14
=32 - (25-24)3-14
=32 - 13-14
=32-1-14=32-15=17
![](https://rs.olm.vn/images/avt/0.png?1311)
\(B=\left(\frac{2}{15}+\frac{5}{3}-\frac{3}{5}\right):\left(\frac{14}{3}-\frac{5}{2}\right)\)
\(B=\left(\frac{2}{15}+\frac{25}{15}-\frac{9}{15}\right):\left(\frac{28}{6}-\frac{15}{6}\right)\)
\(B=\frac{6}{5}:\frac{13}{6}\)
\(B=\frac{6}{5}.\frac{6}{13}\)
\(B=\frac{36}{65}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, -(-5)-(+7)+(+3)+(-8)
= 5 - 7 + 3 + (-8)
= (-2) + 3 + (-8)
= 1 + (-8)
= -7
b, -(-15)-|-10|+|-9|-|5I
= 15 - 10 + 9 - 5
= 5 + 9 - 5
= 14 - 5
= 9
c, 14-(-13)-(17)+(-12)
= 14 + 13 - 17 + (-12)
= 27 - 17 + (-12)
= 10 + (-12)
= 2
d, -|-14| + |-10| - (-12) + (-8)
= -14 + 10 + 12 + (-8)
= (-4) + 12 + (-8)
= 7 + (-8)
= -1
e, -(-11) + (-15) + (13) - 21
bằng 13
X=13 NHA